Chemical constituents from the whole herbs of Peperomia tetraphylla and their chemotaxonomic significance. (June 2021) - Wang, Shuang; De Souza, Cristabelle; Wang, Lu; Zhou, Honglei
Abstract: Our studies report the isolation of seventeen compounds (1–17), which include three phenolic acids (12–14), seven flavonoids (3, 6, 8, 11, 15–17), four secolignans (1, 2, 5 and 9), one tetrahydrofuran lignin (10) and two alkaloids (4 and 7). These compounds have been obtained from the Peperomia tetraphylla using chromatographic methods. Their structures were confirmed based on spectroscopic methods. Among them, five compounds (4, 7, 8, 11 and 15) were found in the family, four compounds (3 and 12–14) were firstly reported from genus Peperomia, and four compounds (6, 9, 16 and 17) were firstly obtained from this species. Furthermore, the chemotaxonomic significance of these ingredients from the whole plants of P. tetraphylla has been discussed in detail. Highlights: Seventeen compounds have been obtained from the P. tetraphylla. The structures of these compounds have been confirmed by spectroscopic methods. tetraphylla is closely related with some plants of the genus Peperomia and Piper. Secolignans can be used as a biomarker of the genus Peperomia.